Simplification in the social service procedure - Hernández Ortega, Citlalli; González-Lozano, Claudia Iveth; Montemayor-Fuentes, Brenda (Política, Globalidad y Ciudadanía, 2020)
This article is the product of a bibliographic review, whose objective was to analyze the evolution and implementation of the administrative and academic procedure of the social service learning unit. The research was non-experimental, since the variable was not manipulated. The design to carry out the research was of the transectional type, since the data collection was only carried out at a single moment in time and included only one variable. The population of interest were students enrolled for Social Service from August 2015 to August 2017, at the Faculty of Political Science and International Relations of the UANL. After the documentary review it was found that; the social service subject is a compulsory learning unit for the eighth semester, of the three degrees taught at the Faculty of Political Science and International Relations, of the Autonomous University of Nuevo León. It is concluded that the subject has facilitated the monitoring and evaluation of the student, the teacher and social service coordinator, as well as the receiving institutions.